ANALISIS JABATAN SEBAGAI DASAR REKRUTMEN UNTUK PENINGKATAN KINERJA SUPERVISOR (STUDI KASUS DI PT. SUKSES ANUGRAH SEJAHTERA) - Imam Setiawan (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2022)
AbstractPT SAS is one of  national facility service company in Indonesia which provide services about cleaning service professional, security service, pest control, and handling managing people. The core business service is professional cleaning service. In data that has been collected, show that performance of Supervisor PT. SAS was bad, which caused by recruitment process that is misfit from job analysis.The purpose of this research is to get job analysis design of supervisor PT SAS in order to improving recruitment efectivity. Theory which is used in this research is perfomance theory, recruitment, dan job analysis.Research method which is used in this research is qualitatif descriptive method. Instrument which is used in this research by quesioner, interview, and observation with 360 degrees session, to get comprehensive information in order to make job analysis design of supervisor PT SAS.The results of research is show comprehensive information about job description and job specification which used as a competency model for recruitment process. Comparing between before and after job analysis have done, it shows that information about qualification of supervisor have many contents about skill, knowledge, and attitude. Before job analysis did’nt do, information about qualification of supervisor is only about skill other characteristic